The impact of pelvic floor contraction on urethral mobility and urogenital hiatus size in pelvic floor ultrasound - Dobek-Brylińska Marta; Wlaźlak Edyta; Wlaźlak Wiktor; Krakowiak Jan; Wróbel Andrzej; Surkont Grzegorz (Journal of Ultrasonography)
The aim of the study was to assess the effect of pelvic floor contraction on urethral mobility and the size of the urogenital hiatus, as well as to compare two ultrasonographic approaches for the assessment of urethral mobility: transperineal with a transabdominal probe and transvestibular with a transvaginal transducer.